Water markets as coupled infrastructure systems: comparing the development of water rights and water markets in Heihe, Shiyang and Yellow Rivers. Issue 8 (17th November 2019) - Svensson, Jesper; Garrick, Dustin E.; Jia, Shaofeng
ABSTRACT: A Coupled Infrastructure Systems perspective is applied to three cases in north-western China to explain how and why water rights systems and water markets have changed since 1949. The evolution of water rights systems has been shaped by periods of water-supply projects and periods that emphasized regulatory and institutional measures to manage water resources. We argue that water supply infrastructure and water markets have been developed not in sequence but in parallel. The development of water diversion projects and nationwide market-oriented water allocation reform programmes will continue to co-evolve in the future as part of complex coupled infrastructure systems.